The specificity of the author strategy in presenting the figure of Lesia Ukrainka in the novel “Iron Water” by M. Laiuk (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The paper clarifies the peculiarities of the author’s strategy in presenting the figure of a famous Ukrainian writer Lesia Ukrainka in the novel “Iron Water” by the modern Ukrainian writer M. Laiuk. The image of Lesia is formed due to the real and fictional stories told about her by people. Numerous concealed characteristics, reflections and legends about the writer add new shades to her personality, which tends to be still unknown to the modern reader. It is emphasized that the author’s strategy of literary interpretation of the poetic image was to show the traces of Lesia Ukrainka in the lives of ordinary mountaineers, whom she visited in 1901. Through these memories, legends and all sorts of stories, a new vision of the writer is built. Ordinary Ukrainians perceive Lesia as a woman with strange behavior, a woman who leads a way of life that is ambiguous to them, because it does not correspond to their own. M. Laiuk focuses on the way how ordinary Ukrainians observe, analyze and evaluate Lesia’s lifestyle and try to understand her in every possible way, strive to get acquainted with her experiences. This research has shown that the whole system of events is built around the real fact of Lesia Ukrainka’s trip to the spa resort, and therefore the plot is multilined and diverse. It is noted that the writer has chosen a rare way of presenting the figure of Lesia Ukrainka, the essence of which is to reveal the significance of the artist-genius in the fate of ordinary Ukrainians. There are many characters in the novel who have dreamed of meeting Lesia Ukrainka all their lives. They expected that when she returned from Burkut she would come to their village and then they could at least see her, if not talk to her. The poetess is perceived as a special, unusual person in the imagination of such dreamers. It has been noticed that Myroslav Laiuk offers many interpretations of one of Lesia Ukrainka’s trips represented in fragments of the stories of Hutsul people, casual travelers and even nuns. On the one hand, it resembles a deep anthropological study of different generations of Carpathian peasants, and on the other hand, it is a unique way of presenting the image of the artist in a literary work. The paper demonstrates the results of the analytical study of the author’s strategy in terms of presenting the figure of the artist. The essence of which is that the writer does not impose his own vision of the artist’s image, but offers his readers to find in the text of the novel those important life meanings of prominent Ukrainians that will be most significant and unique to the modern reader.
Keywords: author’s strategy; unique figure; presentation; artist’s trace; author